STUDY OF REVERBERATION LAG IN X-RAY BINARY GX 339-4 USING NUSTAR - Rafif Kusumawardhana, Naufal
The launch of the first X-ray satellite, Uhuru, in 1971 led to the rapid development in research of X-ray cosmic sources. One such sources is the black hole X-ray binary (BHXB). Transient Low Mass X-ray Binaries (LMXB), a type of BHXB, undergoes a massive increase in luminosity during what is later called its outburst phase. Generally, spectra of an LMXB transient during an outburst consist of two main components, the thermal component and the non-thermal component. The thermal component is explained by the standard accretion disk model, while the non-thermal component is believed to be caused by a ”corona” located near the disk. However no theory has been able to describe the precise geometry and structure of the corona. Several transient LMXBs show a so-called reflection spectrum which is caused by reprocessed and disk-scattered photons. Observations show that, in some transient LMXB, reprocessed photons lagged behind non-reprocessed photons, these lags are later known as reverberation lags. These lags can be used to predict the geometry of LMXB’s corona in a method called reverberation mapping. In this Final Project, using observation data from the NuSTAR mission, the soft and hard light curves will be cross correlated to identify the presence of reverberation lags. The results show that there are indications of reverberation lags in timescales of > 1000s. Previous research show that such lags are present in the timescales of < 1s. However, in timescales of < 1000s, results show a peak lag value of 0 which is most likely caused by the less than optimal time resolution given that the smallest bin size available for standard data processing is 10s